Amplification of olfactory signals by Anoctamin 9 is important for mammalian olfaction. (December 2022) - Kim, Hyungsup; Kim, Hyesu; Nguyen, Luan Thien; Ha, Taewoong; Lim, Sujin; Kim, Kyungmin; Kim, Soon Ho; Han, Kyungreem; Hyeon, Seung Jae; Ryu, Hoon; Park, Yong Soo; Kim, Sang Hyun; et al.
Abstract: Sensing smells of foods, prey, or predators determines animal survival. Olfactory sensory neurons in the olfactory epithelium (OE) detect odorants, where cAMP and Ca 2+ play a significant role in transducing odorant inputs to electrical activity. Here we show Anoctamin 9, a cation channel activated by cAMP/PKA pathway, is expressed in the OE and amplifies olfactory signals. Ano9 -deficient mice had reduced olfactory behavioral sensitivity, electro-olfactogram signals, and neural activity in the olfactory bulb. In line with the difference in olfaction between birds and other vertebrates, chick ANO9 failed to respond to odorants, whereas chick CNGA2, a major transduction channel, showed greater responses to cAMP. Thus, we concluded that the signal amplification by ANO9 is important for mammalian olfactory transduction. Graphical Abstract: ga1 Highlights: ANO9 expressed in the olfactory epithelium augments the odorant-induced olfactory signals via the cAMP/PKA pathway. The amplifying action of ANO9 contributes to olfactory function because Ano9 -deficient mice showed impairment of olfaction. These results now suggest that ANO9 actively participates in the olfactory signaling in the OE.